Frequency of Dyslipidemia in Patients with Lichen Planus: A Comparative Cross-Sectional Study - Khan, Sana; Pirzado, Muhammad Suleman; Kalhoro, Hafiz Bashir Ahmed; Rajper, Nadia; Memon, Sikander Munir; Memon, Faryal Hussain (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the relationship between lichen planus (LP) and dyslipidemia. Methodology: It was a comparative cross-sectional study conducted at the department of dermatology, Liaquat University of Medical & Health Sciences, Hyderabad, from October 2016 to April 2017. The study included both genders aged 20 to 50, including all patients with cutaneous lichen planus of more than one month. Each patient’s blood sample (after 8 hours of fasting) was collected and sent to the LUMHS diagnostic and research laboratory for lipid profile (elevated total cholesterol higher than 200mg/dL and elevated LDL-C higher than 130mg/dL in LP patients). Where a consultant pathologist prepared each report (at least three years of post-fellowship experience), and the presence or absence of dyslipidemia was noted. All of these data were recorded on a specially designed pro forma. Results: Mean age was 31.23±7.27 years. Out of 100 patients, 51 (51.0%) were male and 49 (49.0%) were females with a ratio of 1:1 between males and females. dyslipidemia in A-group was seen in 35 (70.0%) patients while in B-group was seen in 18 (36.0%) patients (p-value = 0.001 and odds ratio = 4.1481). Conclusion: This study concluded that the frequency of dyslipidemia is higher in lichen planus patients compared to healthy individuals. Keywords: Lichen Planus, Cholesterol, Dyslipidemia, Dermatology